Heirloom Eggplant Varieties in Florida - Monica Ozores-Hampton (EDIS)
Eggplant has a colorful heritage. It was first domesticated more than 4,000 years ago. Ancient Chinese crossbred varieties with different shapes and colors. It migrated to Egypt during the 9th to 12th centuries AD, the Moors introduced eggplant to the Spanish, who took the eggplant to South America around 1650, and in 1806, Thomas Jefferson introduced the eggplant to the United States after receiving the fruit from a friend in France. As opposed to the modern-day hybrid cultivars, heirlooms are old cultivars generated by handing down seeds from generation to generation. This 6-page fact sheet is a guide to heirloom eggplant varieties used in Florida. Written by Monica Ozores-Hampton and published by the UF Department of Horticultural Sciences, November 2013.